ORIGINAL PAPER Characteristics of patients with rheumatoid arthritis positive for antiphospholipid antibodies - Walewska, Ewa; Rupiński, Robert; Wojciechowska, Bożena; Filipowicz-Sosnowska, Anna (Reumatologia/Rheumatology, 2006)
The aim of the study was to estimate the prevalence of anticardiolipin antibodies (aCL) in patients suffering from rheumatoid arthritis (RA) and to analyse clinical course of RA according to development of aCL. Methods: We retrospectively analysed 3 groups of patients with rheumatoid arthritis: • aCL(+) – positive for antiphospholid antibodies (n=7); • aCL(-) – negative for aCL (n=32); • aCL(o) – control group (n=142), in which aCL were not estimated. In every case we analysed clinical features from history, physical examination, laboratory data and treatment. Results: Antiphospholipid antibodies are not routinely estimated in patient with RA. The most common reason for examination was data obtained from history concerning thrombo-occlusive events and misscarriages (about 65% of cases). Patients positive for aCL have more advanced radiological changes and higher titers of antinuclear antibodies. There was no significant difference found between aCL(+) and aCL(-) groups in respect to age, sex, duration of the disease, number of swollen and tender joints, DAS 28 and HAQ, laboratory values of sedimentation rate and CRP, morphology and rheumatoid factor. Antiphospholipid antibodies are associated with clinical signs of infections and vasculitis. Conclusion: We suggest that antiphospholipid antibodies should be measure in a wider groups of patients: positive for antinuclear antibodies, with advanced radiological changes (exponent of duration and activity of the disease), and patients with signs of vasculitis. Patients treated with TNFα antagonists demands especially precise control because immunological response and higher frequency of infections can induce anticardiolipin antibodies.